Financing sustainability through Meezan concept: an Islamic economics perspective - Akbar, Mohamed Aslam; Muhamad Ramlan, Anaztasia Natasha; Smolo, Edib (Routledge, 2026)
In this chapter, we dissect the application of meezan in the scope of Islamic Green Finance (IGF) further to understanding of Islamic economics. The meezan as an economic and environmental system is developed based on the Qur’anic and Sunnah values. It represents cosmic balance. The Qur’anic verse, “The heaven He raised, and He imposed the balance” (Qur’an, 55:7) symbolizes balance and equilibrium. This conforms with the maqasid al-Shari’ah (objectives of Shari’ah or Islamic law) which encourage the proper use of the earth’s resources and ensure sustainable environment for the present and future generations. It can also add up to Islamic legal maxims such as ‘Harm must be eliminated’ (al-darar yuzal) and ‘Hardship generates facility’ (al-mashaqqa tajlib al-taysir) and offers tangible guidelines for efficient and sustainable financing. As such, these principles support funding of sustainable projects like renewable energy and encourage innovative Shari’ah-compliant financial products that effectively blend the traditional elements with modern business and enterprise developments. Sustainable financial products include the green sukuk that harness the environment sustainability projects, the waqf-based funds for community and environment enhancement, and musharakah/mudarabah contracts to invest in effective commercially profitable eco-awareness. Case studies reveal ways in which meezan and maqasid al-Shari’ah principles were applied to support sustainable development. These are examples of the exact contribution that Islamic finance plays in the critical green economic shift and lessening the effects on the climate changes. Hence this chapter posits that through the provisions of meezan framework and Shari’ah-compliant and sustainable financial activities, Islamic finance can develop a powerful framework to cope with the global environmental challenges and contribute to a sustainable future. The observations and conclusions of this work contribute significant insights into understanding and practicing Islamic finance and reveal its tremendous capacity for positive impact for a sustainable future.